2015
DOI: 10.1108/jaee-08-2011-0028
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensiveness of internet reporting by Caribbean companies

Abstract: Purpose – The purpose of this paper is to examine the comprehensiveness and determinants of internet reporting by publicly listed Caribbean companies. Design/methodology/approach – In total, 65 companies with common shares listed on one of the four Caribbean stock exchanges, were included in the study. The study examined the relationship between firm characteristics (size, industry affiliation, listing status, and CEO role duality) and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 56 publications
0
16
0
3
Order By: Relevance
“…Table V presents industry wise classification of sample companies based on SIC 2007 industry classification. Several studies (Oyelere et al, 2003;Xiao et al, 2004;Gandia, 2008;Aly et al, 2010) provide empirical support for the presence of industry effect on CIR, while the studies (Bowrin, 2015) failed to establish a significant association.…”
Section: Research Methodology 41 Samplementioning
confidence: 99%
“…Table V presents industry wise classification of sample companies based on SIC 2007 industry classification. Several studies (Oyelere et al, 2003;Xiao et al, 2004;Gandia, 2008;Aly et al, 2010) provide empirical support for the presence of industry effect on CIR, while the studies (Bowrin, 2015) failed to establish a significant association.…”
Section: Research Methodology 41 Samplementioning
confidence: 99%
“…Based on this insight, it seems imperative for models to be built by including countrylevel factors since company-level factors may not be sufficient for explaining the level of voluntary disclosure (Ojah & Mokoaleli-Mokoteli, 2012). In the context of the IFR, Bowrin (2015) has suggested that researchers look at both the country and company-level characteristics when seeking to explain the IFR. Addressing the recommendations of these prior studies (e.g.…”
Section: Ownership Internet Penetration and Ifrmentioning
confidence: 99%
“…Addressing the recommendations of these prior studies (e.g. Bowrin, 2015), we thus endeavour to examine the interrelationship between company-level governance and countrylevel Internet penetration in influencing the IFR practices of companies in the GCC countries. In theory, there are two possible ways in which company-level governance and country-level institutional factors interact in determining strategic decisions involving the IFR.…”
Section: Ownership Internet Penetration and Ifrmentioning
confidence: 99%
“…Both were investigated in a number of studies in different countries. Examples include Cribbean countries (Bowrin, 2015), Egypt (Desoky, 2010 andSamaha andAbdallah, 2012), Jordan (Al Sawalqa, 2012), United Arab Emirates (Alzarouni et al, 2011) and Malaysia (Turmin et al, 2014).…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%